2017
DOI: 10.14699/kbiblia.2017.28.1.209
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Needs and Seeking Behaviors among Korean Mothers of Young Children in the United States

Abstract: Previous studies have noted mothers' roles as active health information seekers, health managers, and caregivers for their family members. However, little is known about health information needs and seeking behaviors among Korean mothers of young children living in the United States. Using paper-based surveys, this study found that vaccination, child dental health, parenting, nutrition and diets, and physical exercise were ranked as the five most important health topics by the Korean mothers of young children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…Most of mothers who visited the primary health care based on this study were around 26-30 years old (26.3%), and had the largest percentage of children 1-2 (62.5%) with the largest age range for children from 1 month to 6 years old. Compared to other studies 5,7 with similar information, where majority of the mothers were in their 30s, and majority of Reyes's study research mothers also has 1-2 children to take care in home. 7 The age of the child is also an important factor influencing mothers' health information needs for their children.…”
Section: Characteristics Of Study's Respondentsmentioning
confidence: 64%
See 4 more Smart Citations
“…Most of mothers who visited the primary health care based on this study were around 26-30 years old (26.3%), and had the largest percentage of children 1-2 (62.5%) with the largest age range for children from 1 month to 6 years old. Compared to other studies 5,7 with similar information, where majority of the mothers were in their 30s, and majority of Reyes's study research mothers also has 1-2 children to take care in home. 7 The age of the child is also an important factor influencing mothers' health information needs for their children.…”
Section: Characteristics Of Study's Respondentsmentioning
confidence: 64%
“…7 The age of the child is also an important factor influencing mothers' health information needs for their children. Lee (2017) 5 studies found that mothers tend to seek more information for their child between the ages of newborn to ten. Around 51.7% of mothers had the senior high school as their last degree, and most of them are housewives (75.4% & 70.3%).…”
Section: Characteristics Of Study's Respondentsmentioning
confidence: 99%
See 3 more Smart Citations